CAN RETURN MIGRATION REVITALISE LATVIA’S REGIONS? FACILITATORS AND BARRIERS TO HUMAN CAPITAL GAINS - Mieriņa, Inta; Bela, Baiba (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Migration researchers from East-Central Europe most often focus on the impact of ‘brain drain’ which is characterised by the loss of human capital from emigration. In this paper focus is placed on the assumption that migrants living abroad gain valuable experiences and education opportunities, that lead to personal growth, facilitate entrepreneurship and psychological resilience, amongst other important skills. This experience may be used for the revitalisation of the less-developed regions the migrants return to. To explore what facilitates or inhibits the fulfil potential of ‘brain circulation’ or gain, we use data from two large-scale surveys of return migrants in Latvia, in-depth interviews, media analysis, regional workshops and secondary data. We find that return migrants often choose to return to the capital city and not their original point of departure. While towns and villages offer some advantages such as little competition, easier adaptation and high neighbourhood quality, reliance on personal contacts distorts the efficiency of job placement and there are fewer work opportunities in one’s acquired profession. The skills are waisted and employers remain unappreciative of knowledge gained abroad in towns and villages more than in Riga.